Proteínas cry12 do bacillus thuringiensis modificadas para o controle de nematódeo - KENNETH E. NARVA; AARONT T. WOOSLEY; TIMOTHY D. HEY (2015)
The subject invention concerns plants protected from nematode feeding damage and improved versions of Cry proteins. The subject invention also concerns improved versions of Cry12A proteins. Synthetic genes encoding these modified proteins are also part of the subject invention. Another embodiment of the subject invention includes plants transformed with the genes of the subject invention. In yet another embodiment the subject invention concerns Bt proteins for in-plant protection against crop damage by root knot nematode (RKN; Meloidogyne incognita) and soybean cyst nematode (SCN; Heterodera glycines).